ANALISIS MANAJEMEN STRATEGIK PERUSAHAAN LE MINERALE - Reza, Kemal; Kamal Hadyan; Alfad Alfarizky; M. Kemal Attatur (Media Riset Bisnis & Manajemen, 2022)
This study aims to determine business strategies for Le Minerale, a company operating in the mineral water industry. Facing rapid market growth and a high demand for adaptation, Le Minerale needs to develop products that are competitive, creative, and innovative. To understand and formulate its business strategies, the study employed the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, SPACE Matrix, and Quantitative Strategic Planning Matrix (QSPM). Findings from the IFE analysis suggest that Le Minerale excels in innovation, marketing, and cost management. The SPACE Matrix indicates financial stability amidst technological and inflationary challenges, prompting an aggressive strategy based on market strengths and production efficiency. Finally, the Quantitive Strategic Planning Matrix (QSPM) analysis advocates for a market penetration strategy to enhance market share and customer loyalty. Managerial implications of this study suggest that Le Minerale should leverage its strengths in innovation and marketing to expand market reach and enhance customer engagement through targeted marketing campaigns and product innovation. Implementing these strategies could help sustain competitive advantage and capitalize on emerging market opportunities.